Improving the probability of pregnancy in endometriosis cases: a study in patients undergoing in vitro fertilization (Faculty of Medicine Universitas Indonesia, 2012)
Background: Endometriosis is the most common condition underlying infertility in women. To increase the rate of pregnancy in women with endometriosis, embryo selection is performed during in vitro fertilization. This study aims to prove the effectiveness of embryo selection on the rate of pregnancy in a hospital in Jakarta. Methods: This is a cross sectional clinical epidemiology study, performed on endometriosis patients who visited the hospital between 2007-2009. Patients were diagnosed with endometriosis using the laparoscopy technique. Embryo selection was performed by assessing the morphology and cell count. Results: We were able to collect data from 72 subjects who underwent IVF during this research period. One subject was dropped out of the program due to immaturity of the oocyte. Successful fertilization was achieved for 65 subjects, but two of them did not undergo embryo transfer. Out of all the subjects undergoing embryo transfer, 26 subjects successfully became pregnant (36.1%). In severe endometriosis cases, pregnancy was achieved with excellent quality embryos (50%) and good-moderate quality embryos (16.7%); but the probability of failure to become pregnant was found to be the same (50%). In mild-moderate endometriosis cases, the probability of pregnancy with excellent quality embryos was 39% compared to 25% chance with good-moderate quality embryos. Regarding the number of embryos that were transferred, we have found that the probability of pregnancy was 50% higher when 3 embryos were transferred, compared to 1 or 2 transferred embryos. Conclusion: This study shows that embryo quality and the number of transferred embryos are relevant to increase the probability of pregnancy in patients undergoing IVF. But because the probability of not achieving pregnancy is not significantly different, we need to find another marker that is more sensitive to assess the quality of embryo transfer. (Med J Indones. 2012;21:147-51)